Diverticular disease of the large intestine: current state of the problem - N. A. Lysov; M. M. Osadchuk; D. V. Balashov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
This review presents modern information on etiopathogenesis, clinic, diagnostics and treatment of diverticular disease of the large intestine (DBTK). Based on the analysis and epidemiological data, this pathology can be attributed to the global epidemic of the 21st century, associated with the Westernization of lifestyle and aging of the population in civilized countries. The described tactics of management of patients with this pathology is based on global trends that have formed in the last decade.